Penggunaan Bahasa Pemrograman Python Untuk Memvisualisasikan Data Peluang Selamat Dari Kecelakaan Titanic - Kalyani Jeslyn Lim; Clement Nathanael; Felicia Angel Wijaya; Jeson Adhi Dharma; Thaddeus Kendrick Andrian; Wilsen Soetresno; Rahmi Yulia Ningsih (Jurnal Publikasi Teknik Informatika, 2023)
Titanic is a cruise known for its grandeur during the past and its tragedy that caused lots of people to die. Until now, its tragedy has drawn the interest of many people towards the ship. As a result, there are many films, documentaries, and books that discuss the tragedy. Titanic is still a research object in many different study fields, including data science. In this article, we analyze a dataset containing samples from the passengers of Titanic to determine the probability to survive the tragedy generally and to test our hypothesis that there are some factors that enlarge the probability to survive. In this research, we use Python programming language to visualize the Titanic dataset. The population of this research is 2.240 people and the sample is 890 people. We use quantitative and qualitative methods to analyze the data. From this research, a person’s chance to survive the Titanic tragedy in general is 0.38, and there are some factors such as age, gender, and cabin class that can enlarge the chance of survival.